2019
DOI: 10.1017/s1366728919000257
|View full text |Cite
|
Sign up to set email alerts
|

Code-switching in young bilingual toddlers: A longitudinal, cross-language investigation

Abstract: Although there is a body of work investigating code-switching (alternation between two languages in production) in the preschool period, it largely relies on case studies or very small samples. The current work seeks to extend extant research by exploring the development of code-switching longitudinally from 31 to 39 months of age in two distinct groups of bilingual children: Spanish–English children in San Diego and French–English children in Montréal. In two studies, consistent with previous research, childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 59 publications
(142 reference statements)
1
24
1
Order By: Relevance
“…As previously discussed, visual word processing speed has been reported to predict vocabulary in monolingual and bilingual children between two and eight years Peter et al, 2019;Smolak et al, 2021). Regarding haptic word processing, to date, only two studies have been conducted and only short-term predictability (from ages 1;4 to 1;10) has been observed in bilinguals (Legacy et al, 2018;Smolak, DeAnda, Enriquez, Poulin-Dubois & Friend, 2019). We extended past work by testing a sample of French-English children with a wide range of second language exposure.…”
Section: Discussionmentioning
confidence: 63%
“…As previously discussed, visual word processing speed has been reported to predict vocabulary in monolingual and bilingual children between two and eight years Peter et al, 2019;Smolak et al, 2021). Regarding haptic word processing, to date, only two studies have been conducted and only short-term predictability (from ages 1;4 to 1;10) has been observed in bilinguals (Legacy et al, 2018;Smolak, DeAnda, Enriquez, Poulin-Dubois & Friend, 2019). We extended past work by testing a sample of French-English children with a wide range of second language exposure.…”
Section: Discussionmentioning
confidence: 63%
“…DETs) and lexical elements (e.g. Ns) in CS has also been argued elsewhere (Dussias, 2002;Jake et al, 2002;Smolak et al, 2020). Jake et al (2002) account for this asymmetry by showing that if DETs were supplied by the EL, the ML would become less 'transparent ' (p. 87).…”
Section: Grammatical Constraints On Cs In Both Languagesmentioning
confidence: 82%
“…In Raichlin et al (2019), the directionality findings were clearly weighted in favor of CS into L2/Hebrew, due to greater exposure to the societal language in the preschool classroom, in the playground, on the street in the children's mixed neighborhoods, and in their homes, where older siblings and even parents all provided Hebrew input. Smolak et al (2020) reported that for some groups of the Spanish-English bilingual children in their study, low exposure to Spanish caused them to codeswitch into English. Similarly, Ribot and Hoff (2014) noted that CS directionality differences in Spanish-English bilingual children were a function of L1 or L2 input: the children who had more English input switched more from Spanish to English, while the children with higher Spanish input switched more from English to Spanish.…”
Section: Directionality In Bilingual Children's Codeswitchingmentioning
confidence: 92%
See 2 more Smart Citations